A Pentecostal Perspective on Theological Implications of the Verbal Inspiration of Scripture - Martin, Lee Roy (Sekolah Tinggi Teologi Intheos Surakarta, 2024)
The doctrine of the inspiration of the Bible is commonly affirmed in the Pentecostal tradition. For the most part, Pentecostal statements regarding Scripture have parroted the views Evangelicalism that focus attention on infallibility and inerrancy. This article suggests that a Pentecostal theology of inspiration is needed that takes into account Pentecostalism’s epistemology, theology of the Holy Spirit, and understanding of prophecy. Utilizing a method that integrates theological interpretation and grammatical exegesis, this study suggests six theological maxims that can be inferred from a Pentecostal perspective on the doctrine of inspiration. These six points are offered as starting points for discussion and for the development of a robust theology of inspiration.